Who supports MO private school choice? Evidence from likely voters in Missouri - Shelton, Amy J.; Anglum, J. Cameron; Rhinesmith, Evan; Burrola, Abigail (Education Policy Analysis Archives, 2022)
In the first half of 2021, 33 states considered new private school choice legislation. Despite this legislative interest, public opinion on private school choice remains varied. In this paper, we examine voter support for private school choice in Missouri, a politically conservative state that lacked a private school choice program until 2021. We conduct a survey experiment to gauge support for the expansion of private school choice to religious schools, assess preferences for universal or targeted student access, and explore opinions regarding the regulation of participating private schools. We find voters are significantly less likely to support voucher expansion when primed to consider that vouchers could be used at religiously affiliated schools. Political ideology, racial identity, college exposure, and family income are significant predictors of voucher support. Regulation support varies widely, with the strongest support for adherence to state testing requirements and the lowest support for waiving admissions requirements for voucher students. We conclude by discussing the implications of our findings for Missouri’s recently passed private school choice program, particularly by considering ways in which political compromise may be reached to implement the program in a manner conscious of heterogeneous voter preferences.